Ultrasmall Pd/Au bimetallic nanocrystals embedded in hydrogen-bonded supramolecular structures: facile synthesis and catalytic activities in the reduction of 4-nitrophenol. Issue 38 (27th August 2015) - Jiang, Feng; Li, Ruimin; Cai, Jianhua; Xu, Wei; Cao, Anmin; Chen, Daiqin; Zhang, Xing; Wang, Chunru; Shu, Chunying
Abstract : A hydrogen-bonded supramolecular structure supported with ultrasmall Au, Pd bimetallic nanoparticles was readily synthesized and showed unusual catalytic properties. Abstract : Melamine cyanurate (MCA) – a kind of hydrogen-bonded self-assembly supramolecular structure material – is readily synthesized by a hydrothermal method. Noble metal nanoparticles (NPs) (Pd, Au bimetallic and monometallic NPs) with an ultrasmall size below 5 nm are homogeneously distributed in the as-prepared MCA via a simple procedure at room temperature without any additional reductant and stabilizer. The as-prepared bimetallic noble metal NPs exhibit good catalytic activities toward the reduction of 4-nitrophenol to 4-aminophenol, and the resulting catalytic activities are even much better than those of monometallic counterparts. This unusual catalytic property should be relevant to the small size of noble nanoparticles and the electronic interaction between the support, Pd and Au nanoparticles.